Shielding properties of CuNiZn ferrite in the radio frequency range - Ruiz, María Sol (2013)
Shielding properties of copper-doped NiZn ferrites in the frequency range 1 MHz-1.8 GHz, were explored. Samples of composition CuxNi 0.4-xZn0.6Fe2O4 with x=0.0, 0.1, 0.2, 0.3 and 0.4, were prepared by the ceramic method. Powders and pellets were sintered at 1100 °C for 2 h. The effect of compositional variation on structural, dielectric and magnetic properties was investigated in order to relate them with the attenuation behavior. X-ray diffraction measurements confirmed the formation of a spinel structure at the selected sintering temperature. The addition of copper promotes grain growth, increases the samples density and modifies saturation magnetization, permeability and permittivity in the explored frequency range. As the reflection loss absolute values (|R L|) for all the samples are above 35 dB, they can all be considered as shielding materials. The optimum attenuation was observed for x=0.2, reaching a maximum |RL| of almost 60 dB at 10 MHz with an attenuation bandwidth of at least 3 MHz. © 2012 Elsevier Ltd and Techna Group S.r.l.